Quality of life and Comprehensive Geriatric Assessment (CGA) in older adults receiving Accelerated Partial Breast Irradiation (APBI) using a single fraction of Multi-Catheter Interstitial High-Dose Rate Brachytherapy (MIB). The SiFEBI phase I/II trial. Issue 7 (September 2021) - Boulahssass, Rabia; Chand, Marie-Eve; Gal, Jocelyn; Dittlot, Claire; Schiappa, Renaud; Rambaud, Cyrielle; Gonfrier, Sebastien; Guerin, Olivier; Hannoun-Levi, Jean Michel
Abstract: Objectives: The SiFEBI trial demonstrated that a post-operative Multicatheter Interstitial Brachytherapy (MIB) appears feasible and with acceptable toxicity in older adults aged 70 years and older presenting with low-risk breast cancer. The aim of the present ancillary study was to analyze the quality of life and Comprehensive Geriatric Assessment (CGA) domains within 6 months in older adults receiving Accelerated Partial Breast Irradiation (APBI) using a single fraction of MIB. Materials and Methods: From 11/2012 to 09/2014, 37 patients were included and 26 were evaluable. Patients (pts) aged 70 years and older with a Balducci score of 1 or 2 and presenting with low-risk breast cancer were prospectively enrolled in this phase I/II trial (NCT01727011 ). After lumpectomy, intra-operative catheter implantation was performed for post-operative APBI after pathological findings. Quality of life (QoL) evaluation and CGA were scheduled at baseline and 1, 3, and 6 months after APBI. Autonomy decline was defined as a 1-point decrease in Activities of Daily Living (ADL). Results: Mean age was 77 years. Within the first 6 months of follow-up, no autonomy decline was observed in ADL, 3 patients had an autonomy decline in Instrumental Activities of Daily Living (IADL) and 2 patients had a slower gait speed but no changes in cognitive function, nutritional status, and depression screening. Global QoL was quite similar at baseline compared to 1, 3, and 6 months. No differences were observed for functional items. Conclusion: APBI based on a single fraction of MIB in older adults with low-risk breast cancer appears to be feasible with a minimal loss of autonomy regarding IADL, no loss of autonomy in ADL, an acceptable decrease in other CGA domains, and with no impact on global quality of life.